Insights Into the Mechanism of Tyrosine Nitration in Preventing β-Amyloid Aggregation in Alzheimer’s Disease - Zhao, Jie; Shi, Qihui; Zheng, Ye; Liu, Qiulian; He, Zhijun; Gao, Zhonghong; Liu, Qiong (Frontiers in Molecular Neuroscience, 2021)
Nitration of tyrosine at the tenth residue (Tyr10) in amyloid-β (Aβ) has been reported to reduce its aggregation and neurotoxicity in our previous studies. However, the exact mechanism remains unclear. Here, we used Aβ1–42 peptide with differently modified forms at Tyr10 to investigate the molecular mechanism to fill this gap. By using immunofluorescent assay, we confirmed that nitrated Aβ was found in the cortex of 10-month-old female triple transgenic mice of Alzheimer’s disease (AD). And then, we used the surface-enhanced Raman scattering (SERS) method and circular dichroism (CD) to demonstrate that the modification and mutation of Tyr10 in Aβ have little impact on conformational changes. Then, with the aids of fluorescence assays of thioflavin T and 4,4′-dianilino-1,1′-binaphthyl-5,5′-disulfonic acid, transmission electron microscopy (TEM), atomic force microscopy (AFM), and dynamic light scattering (DLS), we found that adding a large group to the phenolic ring of Tyr10 of Aβ could not inhibit Aβ fibrilization and aggregation. Nitration of Aβ reduces its aggregation mainly because it could induce the deprotonation of the phenolic hydroxyl group of Tyr10 of Aβ at physiological pH. We proposed that the negatively charged Tyr10 caused by nitration at physiological pH could interact with the salt bridge between Glu11 and His6 or His13 and block the kink around Tyr10, thereby preventing Aβ fibrilization and aggregation. These findings provide us new insights into the relationship between Tyr10 nitration and Aβ aggregation, which would help to further understand that keeping the balance of nitric oxide in vivo is important for preventing AD.